ACCIDENT RISK ANALYSIS USING HIRARC METHOD (HAZARD IDENTIFICATION RISK ASSESSMENT AND RISK CONTROL) AT PT. STARR PANEL INDUSTRY - Rofiq Hidayat (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2023)
Starr Panel Industri is a company that produces sandwich panel materials that are widely used by contractors and infrastructure activists. However, in the production process there is still manual work that can pose a risk of work accidents. Every activity has potential dangers, either due to negligence or lack of implementation of an occupational safety system. Therefore, the implementation of Occupational Safety and Health (K3) management is very important. K3 management is an effort to reduce the risk of accidents that can harm humans, the environment, and the company. The HIRARC method is used in this study as an approach to analyze the risks and directions of the implementation of K3. The results of the study show that this method is effective in assessing and reducing the level of occupational safety risks. Workers' attitudes also play an important role in the effectiveness of the implementation of K3. Factors that affect occupational safety include human factors, work standardization, and the environmentwork, infrastructure facilities such as personal protective equipment, and weather factors. This study advises companies to immediately establish policies or SOPs related to occupational safety and consider productivity variables for future research.